2014
DOI: 10.1039/c3ra44483j
|View full text |Cite
|
Sign up to set email alerts
|

In vitro/In vivo assessment and mechanisms of toxicity of bioceramic materials and its wear particulates

Abstract: With the progress in modern technological research, novel biomaterials are being largely developed for various biomedical applications. Over the past two decades, most of the research focuses on the development of a new generation of bioceramics as substitutes for hard tissue replacement. In reference to their application in different anatomical locations of a patient, newly developed bioceramic materials can potentially induce a toxic/harmful effect to the host tissues. Therefore, prior to clinical testing, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(55 citation statements)
references
References 176 publications
(207 reference statements)
0
54
0
1
Order By: Relevance
“…The experiment was performed to influence the evaluation of the cytotoxicity of the bioactive glass-ceramic samples. The analysis was performed according to the previous literature by the neutral red uptake methodology [29][30][31][32]. Proliferation assay of the cell seeded glass-ceramic materials was performed using MTT (3-(4,5-dimethylthiazol-2-y1)-2,5-diphenyltetrazolium bromide assay (Himedia, Mumbai, India) Assay.…”
Section: In Vitro Cytotoxicity and Cell Proliferation Assaymentioning
confidence: 99%
“…The experiment was performed to influence the evaluation of the cytotoxicity of the bioactive glass-ceramic samples. The analysis was performed according to the previous literature by the neutral red uptake methodology [29][30][31][32]. Proliferation assay of the cell seeded glass-ceramic materials was performed using MTT (3-(4,5-dimethylthiazol-2-y1)-2,5-diphenyltetrazolium bromide assay (Himedia, Mumbai, India) Assay.…”
Section: In Vitro Cytotoxicity and Cell Proliferation Assaymentioning
confidence: 99%
“…The results of the in vitro cytotoxicity tests revealed that for high concentrations of glass powder (10 mg/l), cell mitochondrial activity was significantly reduced for NCL1, NCL3, NCL6 and NCL8 compositions [58], meaning that the NCL2, NCL4 and NCL7 formulations are suitable for further study. No single effect provided a direct correlation between the cytotoxicity and ionic release potential, but a number of observations can be made:

For both the NCL1 and NCL3 formulations, it is most likely that the release of vanadium had a negative effect on cell mitochondrial activity [59], [60].

The NCL6 composition did not contain many dopants, and because the release of Co, Cu and Cr after 28 days in immersion was quite low (data not shown) [61], it is most likely that the high levels of phosphorus and boron were the cause of the detrimental effect of this glass.

No clear reasons for the toxicity of NCL8 were found; hence, the negative effect is most likely due to the combination of the different oxides.

The highly reactive nature of the NCL4 borate-based glass enabled the release of strontium at a higher rate than NCL1 composition, which has been demonstrated to increase proliferation as well as differentiation of osteoblast cells [62], [63].

The positive effect of the NCL7 formulation might derive from the combined effect of titanium, iron and copper, which enhance osteoblasts proliferation and activity [64].

…”
Section: Discussionmentioning
confidence: 99%
“…2,[4][5][6] Though Ti based implants demonstrate standard biocompatibility and mechanical properties, they are not enough to construct the implant worthy and durable for longer period of time in corrosive body environment like body uid. 1-3 Among them, commercially pure titanium (cpTi) and its alloys are well established and have become the gold standard as oral implants for tooth substitutes due to their potential immunologic and promising aesthetic compromises.…”
Section: Introductionmentioning
confidence: 99%